Effect of Calcination Temperature on Microstructure, Porosity and Hardness of Cao/Sio2 Nanocomposites for Bone Implants - Wardatul Ullya; Riri Jonuarti; - Ratnawulan (PILLAR OF PHYSICS, 2022)
This research is a study on the effect of calcination temperature on microstructure, porosity, and hardness of CaO/SiO2 nanocomposites for bone implants made from natural materials of pensi shells and silica sand. The purpose of this study was to determine the effect of variations in calcination temperature on the morphological analysis of structural form, porosity, and hardness of CaO/SiO2 nanocomposites in samples for biomaterials and to determine whether CaO/SiO2 nanocomposites derived from pensi shells and quartz sand are possible to be applied as biomaterials. The results showed that the effect of variations in calcination temperature on the microstructure of bone implant samples was that the higher the calcination temperature would affect the microstructure's shape on the surface of the model where the surface formed was widening, and the grain size was getting smaller. In the porosity, it can be seen that there is diffusion between one grain and another. The grains melt with each other and close the pores from the outside, resulting in compaction at a temperature of 1000°C with a porosity value of 0.005% and the best hardness value of 4.8 kg/mm2.